SEM analysis of agreement with regulating online hate speech: influences of victimization, social harm assessment, and regulatory effectiveness assessment - Park, Ahran; Kim, Minjeong; Kim, Ee-Sun (Frontiers in Psychology, 2023)
In an era where digital interactions are increasingly prevalent, the challenge of effectively regulating online hate speech has emerged as a crucial societal concern. Balancing the regulation of such speech with the preservation of online freedom of expression is a delicate task, requiring broad consensus among internet users. This study delves into the various factors shaping public attitudes towards the regulation of online hate speech in South Korea. Our findings reveal that experiences of victimization by hate speech, online activity such as content uploading, assessment of social harm caused by online hate speech, and assessment on the effectiveness of regulatory measures all play significant roles in garnering support for regulation. Notably, online activity correlates strongly with increased encounters with hate speech. This, in turn, leads to a more profound understanding of its social harm and, consequently, a heightened inclination to support regulatory measures. These insights underscore the growing urgency to address online hate speech, especially as online activity continue to intensify. This study contributes to the discourse on online hate speech regulation by highlighting the complex interplay of personal experience, perceived harm, and efficacy of regulation in shaping public consensus.